2019
DOI: 10.4103/aer.aer_62_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of dexmedetomidine versus midazolam as premedication to propofol anesthesia in endoscopic retrograde cholangiopancreatography

Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is used to diagnose and treat pancreaticobiliary diseases. It is a potentially uncomfortable procedure that needs to be performed under conscious sedation. Safe and effective sedation protocol is the need of an hour. Aims: This study aims to evaluate the requirement of propofol using midazolam and dexmedetomidine as premedication for ERCP. The degree of comfort experienced by endoscopist and the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…This effect may be due to the higher doses of the drug, and decreased sympathetic outflow and circulating catecholamine levels [21]. Gastrointestinal endoscopy studies using dexmedetomidine and midazolam showed that the two agents do not differ from each other in terms of hypoxia, bradycardia and hypotensive effects [22]. Again, in this meta-analysis, patients who were treated with dexmedetomidine for longer procedures, such as ERCP or endoscopic mucosal resection, reported less restlessness [23].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This effect may be due to the higher doses of the drug, and decreased sympathetic outflow and circulating catecholamine levels [21]. Gastrointestinal endoscopy studies using dexmedetomidine and midazolam showed that the two agents do not differ from each other in terms of hypoxia, bradycardia and hypotensive effects [22]. Again, in this meta-analysis, patients who were treated with dexmedetomidine for longer procedures, such as ERCP or endoscopic mucosal resection, reported less restlessness [23].…”
Section: Discussionmentioning
confidence: 83%
“…Recovery times between the two groups are very similar. The reason for this is that we have worked with a very experienced (> 3000 cases) gastroenterologist because the duration of the procedure in our study is relatively short compared to other studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…11,31,32 Recently, some researchers have studied the efficacy and safety of using dextromethorphan as an adjuvant to propofol. 16,33,34 A synergistic effect on sedation was observed in all these studies, in which the total propofol requirement in the dexmedetomidine group was significantly reduced. In this study, we demonstrated that a combination of propofol and dexmedetomidine decreased the EC 50 of propofol by TCI during gastrointestinal endoscopy.…”
Section: Discussionmentioning
confidence: 70%
“…It was reported that dexmedetomidine provided sedative and analgesic 30 effects without the risk of respiratory depression 11,31,32 . Recently, some researchers have studied the efficacy and safety of using dextromethorphan as an adjuvant to propofol 16,33,34 . A synergistic effect on sedation was observed in all these studies, in which the total propofol requirement in the dexmedetomidine group was significantly reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, this is achieved with a reduced occurrence of respiratory depression, in case of dexmedetomidine. [ 20 21 22 23 24 ] However, there are concerns regarding cardiovascular adverse events of dexmedetomidine, such as bradycardia and hypotension. This can prevent its more widespread use during common procedures such as flexible bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%